RESPONDING TO SHAME WITH SOLIDARITY: Sex Abuse Crisis in the Indian Catholic Church - Joseph, Jaisy A. (Asian Horizons, 2020)
By analysing the clerical sex abuse crisis through the lens of shame, the Indian Catholic Church will be better equipped to identify unhealthy patterns of internalization and deflection that prevent healing in the aftermath of these traumatic wounds. In this article, I first explore the issue of gendered violence in the Indian context and how the pervasiveness of shame transforms survivors into scapegoats. I then consider the relational nature of shame and its connection to the institutional church’s temptation towards insularity. Finally, I explore how solidarity through a preferential option for survivors mitigates the internalization of shame by survivors and challenges the irresponsible deflection of shame by the institutional church so that both may journey together toward healing.